2022
DOI: 10.1037/cdp0000482
|View full text |Cite
|
Sign up to set email alerts
|

The markings of linked fate among Asian Americans and Latinxs.

Abstract: Objective: Linked fate, or the degree to which individuals feel that their lives are tied to other group members' lives, can mobilize collective action and strengthen commonalities. Yet, linked fate remains underresearched, particularly among Asian Americans and Latinxs. Method: Using the 2016 Collaborative Multiracial Postelection Survey, the present study draws on García Coll et al.'s (1996) integrative model to examine associations between three domains of linked fate (immigrant, minority, coethnic) and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…The integrative model developed by Coll et al [ 27 ] casts valuable light on the relationship between ethnic minority adolescents’ perceived discrimination and their developmental outcomes. Taking an ecological approach, the model stresses that such adolescents’ development should be considered in terms of the environmental practices of racism, prejudice, and discrimination that factor into their development [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The integrative model developed by Coll et al [ 27 ] casts valuable light on the relationship between ethnic minority adolescents’ perceived discrimination and their developmental outcomes. Taking an ecological approach, the model stresses that such adolescents’ development should be considered in terms of the environmental practices of racism, prejudice, and discrimination that factor into their development [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings also offer support for our hypotheses concerning the positive impact of education and exposure to discrimination. Previous studies examining markers of linked fate among Asian Americans have shown that indicators of social exclusion (e.g., perceived discrimination) and higher educational attainment are associated with Asian linked fate (Kiang et al., 2021; Lu & Jones, 2019). Finally, Hmong, Korean, and Chinese are more likely than Filipinos to feel a sense of linked fate with other Asians in the United States.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that socio‐structural factors have disparate effects on perceptions of group consciousness among racial and ethnic minority groups, including Asians and Asian Americans (Lopez & Espiritu, 1990; Masuoka, 2008; Stokes, 2003) For example, while females are less likely than males, older people and the employed are more likely to adopt panethnic identities such as “Asian American” (Lien et al., 2003). In addition, higher incomes and educational attainment appear to be important toward increasing linked fate among Asian Americans (Kiang et al., 2021; Masuoka, 2006). More educated Asian Americans may express a stronger sense of group consciousness, especially when it comes to believing Asians share a common race and culture as well as similar political and economic interests.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, many Latinos may think of themselves, for example, more as Mexican or Colombian than as Latino, and many Asians may think of themselves more as Chinese or Vietnamese than as Asian; this can mean that members of these groups have multiple identities and, hence, multiple potential linked fatesone for their country-of-origin, another for their broad-based ethnic/racial identity (Sanchez and Masuoka 2010;Rouse, Wilkinson, and Garand 2010). But even with this caveat, there is a body of research suggesting that linked fate does apply to Latinos (Gay, Hochschild, and White 2016;Sanchez and Vargas 2016;Vargas, Sanchez, and Valdez 2017;Shaw, Foster, and Combs 2019;Kiang, Wilkinson, and Juang 2021) and Asians (Masuoka 2006;Lien, Conway, and Wong 2004;Gay et al 2016;Kiang et al 2021). Moreover, the concept of linked fate has been found to be applicable to Muslim Americans (Barreto, Masuoka, and Sanchez 2008).…”
Section: Theoretical Argumentmentioning
confidence: 99%
“…2016; Kiang et al. 2021). Moreover, the concept of linked fate has been found to be applicable to Muslim Americans (Barreto, Masuoka, and Sanchez 2008).…”
Section: Theoretical Argumentmentioning
confidence: 99%